The effects of increased compulsory school leaving age on the teenage fertility of Roma women, a disadvantaged ethnic minority - Anna Adamecz-Völgyi; Ágota Scharle (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2018)
This paper examines the effects that an increase in compulsory school-leaving (CSL) age has on the teenage fertility (both motherhood and pregnancy) of Roma women, a disadvantaged ethnic minority in Hungary. We use a regression discontinuity design identification strategy based on exact date of birth. Increasing the CSL age from age 16 to 18 decreased the probability of teenage motherhood among Roma women by 6.8 percentage points. The higher CSL age delayed first birth-giving by two years. We exploit a unique database that covers live births, miscarriages, abortions, and still births, and contains information on the time conception precise to the week.We propose that the impact of the legislative change can be explained by the incapacitation effect of education: the higher CSL age decreases the probability of getting pregnant during the school year but not during summer and Christmas breaks.
Keywords: J13; C21; I26; 330; education; compulsory school leaving age; teenage fertility; disadvantaged ethnic minorities; regression discontinuity design